Cardiac autonomic response during recovery using whole-body vibration after maximal cardiopulmonary exercise test - Olivares Arancibia, Jorge Eduardo.; Solís Urra, Patricio.; Porras López, Felipe.; Federeci Diáz, Inti.; Rodríguez Rodríguez, Fernando.; Zavala, Juan Pablo; Cristi Montero, Carlos. (Federación Española de Docentes de Educación Física, 2021)
In the last years the nervous and cardiovascular response to exercise has taken on an important relevance, both in sport and health field. In this line, accelerating cardiovascular appears to play a key role in various sports fields. The study aims to examine and compare the acute effect of whole-body vibration (WBV) on cardiac autonomic response after maximal exercise in university runners and physical education student. Twenty men participated in a cross-over study, 10 university runners team (UR) and 10 physical education student (PES) with ages around 18 to 24 years. In each condition, was perform an incremental cardiopulmonary exercise test followed (i) active recovery time using WBV (25 Hz and peak displacement of four mm) and (ii) passive recovery period (no WBV; 0 Hz-0 mm), separated by seven days. Active recovery consisted in one minute seated using WBV and one minute no WBV by six times (12 minutes) more five minutes of passive recovery, and passive recovery consisted in 17 min seated on platform without vibration. Active recovery had significant differences compare to passive recovery (P<0.05). Furthermore, in active recovery, PES had better heart rate response than UR group, however results were not significative. There was not a clear relation between the lineal components of heart rate variability (HRV) in our results. WBV has positive effect in participant's recovery, however, is necessary establish protocols about the intensities and time adequate for allow accelerate recovery the parasympathetic reactivity, for that reason yet can't conclude clearly respect to the more effectivity intensity WBV depending to characteristic of subject.
Respuesta cardiaca autónoma durante la recuperación utilizando vibración de cuerpo completo, después de una prueba de ejercicio cardiopulmonar máxima
Keywords: Active and Passive Recovery; Heart Rate Variability; Physical education student; University runners; Vibrating Platform